2010
DOI: 10.1107/s0909049510011106
|View full text |Cite
|
Sign up to set email alerts
|

Quasiin situNiK-edge EXAFS investigation of the spent NiMo catalyst from ultra-deep hydrodesulfurization of gas oil in a commercial plant

Abstract: Ni species on the spent NiMo catalyst from ultra-deep hydrodesulfurization of gas oil in a commercial plant were studied by Ni K-edge EXAFS and TEM measurement without contact of the catalysts with air. The Ni-Mo coordination shell related to the Ni-Mo-S phase was observed in the spent catalyst by quasi in situ Ni K-edge EXAFS measurement with a newly constructed high-pressure chamber. The coordination number of this shell was almost identical to that obtained by in situ Ni K-edge EXAFS measurement of the fres… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
8
0

Year Published

2012
2012
2018
2018

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 49 publications
2
8
0
Order By: Relevance
“…Co9S8 formation can be minimized by application of a chelating agent, such as citric acid, to the impregnation solution, which has been reported to stabilize Co and Mo precursors at the catalyst surface and facilitate a high degree of promotion of Co in the resulting MoS2 structure[56,90,96].The catalytic activity repeatability test (see section 3.3.1 andFigure 6) might thus be improved by altering the catalyst preparation procedure.For NiMo, the EXAFS results obtained at the Ni K-edge indicated the presence of a NiMoS phase.The Ni-S CN of 3.60 with bond length 2.22 Å is similar to the results obtained by Rochet et al[97] for a sulfided NiMo/Al2O3 catalyst, which was prepared with approximately the same metal loading per nm 2 available support surface area as for this work. The Ni K-edge XANES spectrum for the sulfided catalyst (see supplementary information,Figure S.4), showed similar features as the NiMoS XANES spectrum reported in literature[98]. Furthermore, a small bump at ≈ 8352 eV corresponded to the white line characteristics of NiAl2O4 indicating some interaction of Ni with the MgAl2O4 support.…”
supporting
confidence: 79%
“…Co9S8 formation can be minimized by application of a chelating agent, such as citric acid, to the impregnation solution, which has been reported to stabilize Co and Mo precursors at the catalyst surface and facilitate a high degree of promotion of Co in the resulting MoS2 structure[56,90,96].The catalytic activity repeatability test (see section 3.3.1 andFigure 6) might thus be improved by altering the catalyst preparation procedure.For NiMo, the EXAFS results obtained at the Ni K-edge indicated the presence of a NiMoS phase.The Ni-S CN of 3.60 with bond length 2.22 Å is similar to the results obtained by Rochet et al[97] for a sulfided NiMo/Al2O3 catalyst, which was prepared with approximately the same metal loading per nm 2 available support surface area as for this work. The Ni K-edge XANES spectrum for the sulfided catalyst (see supplementary information,Figure S.4), showed similar features as the NiMoS XANES spectrum reported in literature[98]. Furthermore, a small bump at ≈ 8352 eV corresponded to the white line characteristics of NiAl2O4 indicating some interaction of Ni with the MgAl2O4 support.…”
supporting
confidence: 79%
“…Nevertheless the XANES spectra of catalysts are superimposable neither to the one of the Ni 3 S 2 reference nor to the spectra of NiS and NiS 2 reported in the literature. 63,64 Actually the shape of the XANES spectra of the sulfide catalysts is very similar to the one published by Hamabe et al 65 for a homemade sulfide NiMo/Al 2 O 3 catalyst (Ni/Mo = 0.2), which was identified as representative of the active NiMoS phase 66 by the analysis of RT EXAFS data in an extended k-range. It is nevertheless important to note that, as for the spectrum reported by Hamabe et al, the XANES spectra reported for the calcined sulfided catalysts (calc-sulf-NiMo and dehydrated-calcsulf-NiMo) display at 8353 eV a small bump that we ascribe as a reminiscence of the white line characteristic of the NiAl 2 O 4 -type species.…”
Section: Resultsmentioning
confidence: 65%
“…It corresponds to a shell of 3.1 ± 0.8 sulfur atoms at 2.21 Å (Table S2), which could be consistent with the decoration of Ni at the edges of MoS 2 slabs. Although no direct evidence of the formation of the mixed NiMoS species with a significant identification of a Ni–Mo contribution arises from the EXAFS fitting of the spectrum recorded at 400 °C, the comparison of its XANES spectrum is clearly different from the spectrum measured for monometallic nickel sulfidic NiS x species supported on δ-alumina prepared and sulfided in the same conditions that the sample studied herein (Figure S10). This strongly suggests that in addition to the expected formation of NiS x species, , even if no quantification can be done from the presented data, the active NiMoS phase is also formed upon sulfidation of the studied catalyst.…”
Section: Resultsmentioning
confidence: 84%